2022
DOI: 10.3390/en15030742
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Design and Heat Transfer Performance of Enhanced Closed-Loop Geothermal Systems

Abstract: Geothermal energy is one of the primary sources of clean electricity generation as the world transitions away from fossil fuels. In comparison to enhanced geothermal methods based on artificial fracturing, closed-loop geothermal systems (CLGSs) avoid seismicity-induced risk, are independent of reservoir permeability, and do not require the direct interaction between the fluid and the geothermal reservoir. In recent years, the development of CLGS technologies that offer high energy efficiencies has been explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The need for fossil fuel-based energy has grown due to the world's expanding population and growing reliance on modern technology [1]. The extensive use of fossil fuels has led to many climate problems and much environmental pollution, which are constantly changing our living environment.…”
Section: Introductionmentioning
confidence: 99%
“…The need for fossil fuel-based energy has grown due to the world's expanding population and growing reliance on modern technology [1]. The extensive use of fossil fuels has led to many climate problems and much environmental pollution, which are constantly changing our living environment.…”
Section: Introductionmentioning
confidence: 99%
“…Alimonti et al (2018) reviewed modelling of DBHE systems with a focus on their design and performance for heat and/or electricity generation. Advanced Geothermal System (AGS) technologies, to which DBHEs belong, have been reviewed by Budiono et al (2022), but their work does not include deep BTES. This work therefore aims to provide a comprehensive review on numerical and analytical modelling of closed-loop conventional (vertical) DBHEs and their various applications in heating, cooling and storage, including those not captured by Sapinska- Sliwa et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2000, research has focused on geothermal energy production and avoiding brine extraction using CLG as the deep borehole heat exchanger. Budiono et al [2] reported a substantial growth in papers during the period 2016-2021. This growth is the result of searches for new technologies and technical solutions to increase geothermal applications.…”
Section: Introductionmentioning
confidence: 99%
“…Their systematic review studied different CLG configurations, as reported by [2]. Two main types emerged: The first is the concept of a coaxial exchanger, which can be vertical (DBHE) or developed with a horizontal terminal part (DBHEh); and the second is the U-loop scheme, which includes a geometry composed of two pseudo-vertical sections joined by a horizontal branch (ULHE).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation